Mechanism of the antioxidation effect of α-Fe2O3 on silicone rubbers at high temperature. Issue 10 (19th January 2016) - Fei, Hua-Feng; Han, Xiaojie; Liu, Bozheng; Gao, Xiyin; Wang, Qian; Zhang, Zhijie; Xie, Zemin
Abstract : The high temperature resistance of silicone rubber (SR) could be significantly improved by adding hematite (α-Fe2 O3 ). Abstract : The high temperature resistance of silicone rubber (SR) could be significantly improved by adding hematite (α-Fe2 O3 ). In this study, the variation of α-Fe2 O3 and polysiloxanes was investigated by ultraviolet-visible absorption spectroscopy, X-ray diffraction, Mössbauer spectroscopy, and 29 Si NMR spectroscopy after SR aging for 12 h in air at 350 °C. The results indicate that Fe 3+ is reduced to Fe 2+ by organic free radicals (R˙) in the process of aging. Fe 3+ captures R˙ to protect the polysiloxanes from being destroyed and is transformed into Fe3 O4 . Moreover, magnetic Fe3 O4 is only found in the inner layer of SR; however, it is not detected in the outer layer. Therefore, a new mechanism of antioxidation is proposed: on the outer part of SR, the reduction–oxidation cycle of Fe 3+ is formed because of sufficient oxygen; however, inside the SR, α-Fe2 O3 is gradually reduced to Fe3 O4 .